Utilização das tecnologias assistidas na concepção, no desenvolvimento e no projeto de uma escova dental sustentável e ergonômica - Silva, Letícia Alcará da [UNESP]; Jurisato, Augusto Seolin [UNESP]; Hellmeister, Luiz Antonio Vasques [UNESP] (My University, 2014)
The toothbrush is identified as one of the most importants inventions in human history. Most of them are made by polypropylene, a recyclable polymer. Some are made of polypropylene and polyethylene leftovers from others industrial processes. However, the toothbrushes are discarded incorrectly and end up in landfills, which could be avoided by using a material and design suitable for the manufacture of the product. This study aimed, based on research, develop and design a toothbrush model with great features. For the conception of the prototype, was used rapid prototyping technologies. With the intention of improving the product quality, was created an ergonomic, sustainable and environmentally friendly model, seeking maximally reduce the generation of waste and environmental damages. The solution adopted was the use of "interchangeable head", which can be discarded after their useful life, keeping the rest of the body.
Keywords: Design; Toothbrush; Sustainability; Rapid prototyping; CNC; Bamboo